PENINGKATAN MOTIVASI DAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI PENCEMARAN LINGKUNGAN MELALUI MEDIA FOTONOVELA - Astuti, Puji (Universitas Muria Kudus, 2017)
The research problems are how fotonovela group discussions media can increase motivation and creative thinking abilities of students in the matter of environmental pollution. This study was conducted in two cycles each cycle consist of 2 meetings. Research subjects is motivation and creative thinking abilities of students of class X IPA 8 SMA 1 Kudus semester of academic year 2012/2013. The results showed an increase in motivation and creative thinking abilities of students on material environmental pollution by fotonovela group discussions media.